Daily effects of continuous ICT demands on work–family conflict: Negative spillover and role conflict. (10th June 2020) - Cho, Seonghee; Kim, Sooyeol; Chin, Sean W.; Ahmad, Unber
Abstract: Growing concerns about intensive information and communication technology (ICT) use led to abundant research on its debilitating effects on employees' abilities to meet family demands. Drawing on the stressor–strain model, we conducted a daily diary study to investigate how different types of daily ICT demands experienced during work hours and after work influence work–family conflict (WFC) in the evening. We collected data from 98 full‐time employees (793 day‐level observations) for 10 consecutive workdays to understand employees' work‐nonwork interface experiences, namely, negative spillover and role conflict. First, we examined a multilevel mediation model to test the negative spillover effect of on‐the‐job ICT demands on WFC in the evening via negative affect (NA) at the end of the workday. Second, we investigated the effects of off‐the‐job ICT demands on WFC to provide evidence of role conflict in the nonwork domain. Further, we tested the protective role of boundary control in these phenomena. The multilevel analysis results revealed that different types of ICT demands experienced at work have idiosyncratic impacts on WFC. Also, while extended availability after work hours yields greater WFC, this link was weaker for the employees who perceive high boundary control.